2020
DOI: 10.31234/osf.io/xn9ey
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Like a rug had been pulled from under you”: The impact of COVID-19 on teachers in England during the first six weeks of the UK lockdown

Abstract: Background: On 20th March 2020, in response to COVID-19, UK schools were closed to most pupils. Teachers were required to put remote teaching and learning in place with only two days’ notice from the government. Aims: The current study explores teachers’ experiences of this abrupt change to their working practices, and during the 5-6 weeks that followed. Sample: Twenty-four teachers from English state schools were interviewed, representing mainstream primary and secondary schools and a range of years of experi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 29 publications
(33 reference statements)
6
49
1
7
Order By: Relevance
“…Our results indicated that those teachers who were younger, participated in epidemic prevention and control, had deterioration in parent-child relationship, held negative thoughts of distant teaching/prolonged school closure, spent less time with family or had increased workload had higher risk of depression. These teachers faced enormous pressure due to high workload, low income, fears of infection, uncertainty about how long they will last, low familiarity with remote education and lack of family (36), all of which were source of stress, which reduces the overall physical and mental well-being of teachers and leads to unpleasant emotions, such as depression (7). This may have led to the findings.…”
Section: Discussionmentioning
confidence: 96%
“…Our results indicated that those teachers who were younger, participated in epidemic prevention and control, had deterioration in parent-child relationship, held negative thoughts of distant teaching/prolonged school closure, spent less time with family or had increased workload had higher risk of depression. These teachers faced enormous pressure due to high workload, low income, fears of infection, uncertainty about how long they will last, low familiarity with remote education and lack of family (36), all of which were source of stress, which reduces the overall physical and mental well-being of teachers and leads to unpleasant emotions, such as depression (7). This may have led to the findings.…”
Section: Discussionmentioning
confidence: 96%
“…Adnan & Anwar, 2020;Bal et al, 2020). Another line focuses on teachers-their coping mechanisms, managing burnout risk, and transformative experiences (among others Hargreaves & Fullan, 2020;Kim & Asbury, 2020;Moss et al, 2020).…”
mentioning
confidence: 99%
“…The stress that these school closures put on teachers was felt globally. Kim and Asbury (2020) studied teachers in England during the COVID-19 closures. One of their participants described the experience "like a rug had been pulled from under you" (p. 7).…”
Section: Background and Literaturementioning
confidence: 99%
“…For instance, teachers in England reported that reliable internet was inaccessible to marginalized students. Kim and Asbury (2020) quoted one of their participants:…”
Section: Internet Is Inaccessible To Remote and Marginalized Learnersmentioning
confidence: 99%